Social Assistance in Five Countries in North-Western Europe - Hans Hansen; Marie Louise Schultz-Nielsen (Institute for the Study of Labor (IZA), 2015)
In this paper, we calculate the disposable incomes in 2012 of three selected family types receiving social assistance in five countries in north-western Europe. We also calculate the net replacement rates for families receiving social assistance, calculated on the basis of the disposable incomes of 'average workers' in the five countries, as reported by the OECD. The results show that the Danish social assistance benefits are the highest, or among the highest, of the five countries; Swedish benefits are the lowest or among the lowest, but very much in line with those in Germany. The benefits in the United Kingdom for families with children are in the middle of the group, whereas the UK's benefits for single persons without children are among the lowest. In the Netherlands the picture is more mixed; for single persons without children the benefits are among the highest, for lone parents they are around the middle, and for couples with children the benefits are comparatively low.
Keywords: J38; J65; I38; 330; unemployment; net replacement rate; social assistance benefits